Effects of mixed-culture fermentation on bioactive compounds, antioxidant capacity, and flavor metabolomics of red sour soup - Yuke Liu; Yanping Cui; Lan Cheng; Yingying Wang; Yan Ding; Shuhong Ye (International Journal of Food Microbiology, 2026)

Trace element concentrations and tissue distribution in cetaceans from different ecological groups in Chinese waters - Yaoyao Shi; Hao Cheng; Fanyu Lin; Yang Liu; Cai Lin; Yi Liu; Yan Tan; Qianhui Zeng; Yuke Zhang; Xianyan Wang; Liyuan Zhao (Environmental Pollution, 2026)

Quantifying ecological memory effects to improve climate impact assessments on vegetation growth: A case study of Northeast China - Han Wang; Yuke Zhou; Hao Zhang; Luyu Yan (Environmental Impact Assessment Review, 2026)

Synergistic dual ring-cleavage pathways enable efficient degradation of chlorobenzenes by Pseudomonas putida BS-1 in groundwater - Ji Ouyang; Yuke Luo; Fei Gu; Yan Zhou; Changzheng Cui (Journal of Hazardous Materials, 2026)

Post-marketing safety profile of palivizumab: a 20-year pharmacovigilance study using the FDA Adverse Event Reporting System (FAERS) - Qing Yan; Yuke Zhong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Palivizumab is an FDA-approved monoclonal antibody for preventing severe respiratory syncytial virus (RSV) infections in high-risk children. However, its real-world safety profile, particularly beyond clinical trial populations, remains incompletely characterized. This study aimed to systematically analyze adverse events (AEs) associated with palivizumab using two decades of data from the FDA Adverse Event Reporting System (FAERS) to identify known, novel, and rare safety signals. This study aimed to characterize the post-marketing safety profile of palivizumab and identify AE signals using 20 years of FDA Adverse Event Reporting System (FAERS) data. A retrospective pharmacovigilance study was conducted using FAERS data from Q1 2004 to Q2 2024. Duplicate reports were removed, and palivizumab-related AE reports (primary suspected drug) were extracted. AEs were standardized via MedDRA v27.0 and categorized by system organ classes (SOCs) and preferred terms (PTs). Disproportionality analyses, including reporting odds ratio (ROR), proportional reporting ratio (PRR), multi-item gamma Poisson shrinker (MGPS), and Bayesian Confidence Propagation Neural Network (BCPNN), were used to detect signals, with predefined criteria for signal validation. Among 21,558,936 total FAERS reports, 14,120 (0.065%) palivizumab-related AE cases were included, predominantly in infants aged 28 days–23 months (45.92% of all cases); 51.74% of cases with known sex were male. The most frequent serious outcome was hospitalization (60.98%), followed by death (12.12%). Three system organ class–level positive signals were identified, including two novel signals (Infections and infestations; Congenital, familial and genetic disorders). The strongest preferred term–level positive signals were RSV-related events, with novel signals including infantile spitting up, post-tussive vomiting, oligodipsia, and Kawasaki’s disease. This 20-year real-world study confirms known AEs of palivizumab and identifies novel signals, particularly in infection-related and congenital disorder categories. These findings do not establish causality but highlight the need for prospective studies to validate associations, guiding safer clinical use in high-risk pediatric populations.

The role of autophagy in mycotoxin-induced toxicity: A review - Yuke Xu; Mengjie Liu; Jiashe Chen; Zeyu Liu; Shuya Ma; Yeqiang Liu; Guorong Yan; Xiaoxiang Xu (Toxicology, 2026)

Sulfur-doped carbon for enhanced flue gas desulfurization: Synergistic experimental and DFT insights - Jun Li; Xiang Wang; Xiao Zhu; Yuke Li; Min Yan; Yang Ma; Ping Cui; Jingcai Chang; Liqiang Zhang; Tao Wang; Chunyuan Ma; Zhanlong Song (Fuel, 2026)

Evaluation of seismic performance of prefabricated underground mid-partition walls connected by UHPC grouting sleeves - Zhen Huang; Yuke Luo; Caichao Wei; Bin Liu; Ning Li; Jianguo Dang; Zhanshuo Yan (Tunnelling and Underground Space Technology, 2026)

Chlorine-resistant bacteria in drinking water system: Detection characteristics, identification, and chlorine resistance mechanisms - Chicheng Yan; Xuan Ni; Yuke Luo; Ziwei Han; Bingbing Guo; Changzheng Cui (Journal of Hazardous Materials, 2026)

An egg-tray structural interface photothermal evaporator based on carbonized waste cotton and electrospun recycled PET - Yuke Niu; Xiaoyu Jia; Yushan Li; Yuqing Wang; Xu Yan (Chemical Engineering Journal, 2025)

Genesis of the South Pit Deposit in Jiama District, Tibet: Constraints from Geology, Geochronology and Amphibole Geochemistry - Pan Tang; Juxing Tang; Bin Lin; Aorigele Zhou; Faqiao Li; Xiang Fang; Jing Qi; Mengdie Wang; Yan Xiong; Yuke Xie; Zhengkun Yang; Xiaofeng Yao (Journal of Earth Science, 2025)

Association between meteorological factors and varicella incidence: a multicity study in Yunnan Province, China - Hao Wang; Shanjun Huang; Zhaohan Wang; Hua Zhen; Zhuo Li; Wenqi Fan; Menghan Lu; Xin Han; Lanping Du; Meifang Zhao; Yuke Yan; Xinyao Zhang; et al. (Environmental Science and Pollution Research, 2023)

Can planned control measures for private passenger vehicles achieve China's carbon peak goal and mitigate the environmental impact? - Dan Zeng; Yan Dong; Huajun Cao; Yuke Li; Bernard Hon; Cuimei Ma; Chris Yuan; Michael Z. Hauschild (Resources, Conservation and Recycling, 2023)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)